Pengaruh Good Corporate Governance, Persentase Saham Publik dan Leverage Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Listing di Bursa Efek Indonesia (BEI) dengan Periode IPO 2011-2015) - Fatimatuz Zahroh; Fitri Ella Fauziah (Accounting Study Program, Faculty of Economics and Business, 2017)
This study aims to examine the effect of Good Corporate Governance in terms of institutional ownership, managerial ownership, audit committee, independent commissioner, percentage of public shares and leverage on earnings management in companies conducting Initial Public Offering (IPO). This research is classified as pure quantitative research. This research was conducted using purposive sampling method so that a sample of 67 companies was obtained. The data analysis method used in this study is multiple linear regression analysis using the SPSS version 20 analysis tool. Based on the results of the analysis, it is found that Good Corporate Governance seen from institutional ownership has a negative influence on earnings management in companies that carry out IPOs; Good Corporate Governance seen from managerial ownership has a positive influence on earnings management in companies conducting IPOs; Good Corporate Governance seen from independent commissioners has a positive influence on earnings management in companies conducting IPOs; Good Corporate Governance seen from the audit committee has a positive influence on earnings management in companies conducting IPOs; Good Corporate Governance seen from institutional ownership has a negative influence on earnings management in companies conducting IPOs; Good Corporate Governance seen from institutional ownership has a negative influence on the earnings management of companies conducting IPOs.